EFICÁCIA ADAPTATIVA DE ADOLESCENTES UNIVERSITÁRIOS TRABALHADORES - Garcia, Alessandro Tadeu (2011)
Simon (1989) defines adaptation as the set of responses of a living organism, at various times, the situations that change, allowing maintenance of their organization compatible with life. This study aimed to evaluate the effectiveness of adaptive of adolescent students; to assess possible differences in the quality of adaptation among adolescents university workers and not workers; and identify, through EDAO, present and the factors determining the quality of the adaptation of a teenage worker and not an employee. To that end, we first applied the Adaptive Operationalized Diagnostic Questionnaire in 144 new students from a private university in the Greater ABC of both genres and periods, with 115 females and 29 males and 85 in the morning and 59 the night of 17 to 20 years old, with 46 to 98 work and study and study only. After evaluating the Questionnaire, two students were chosen to implement the Adaptive Diagnostic Scale Operationalized. The first, aged 19, student of the morning and did not work, was chosen to present the lowest average of the group, presenting evidence of adaptation ineffective, and the second university to be a worker of 18 years, with indications of effective adaptation. The results showed that there is no statistically significant difference in the quality of the adaptation by considering the variables of industry adaptation, work, age, gender and course, with the exception of the gender variable in Socio-cultural sector, in which it was evident that women are significantly more appropriate than boys. The data revealed that 100 participants (69.4%) had 3 points, and had the diagnostic classification Moderate Inefficient Adaptation (Group 3), 27 (18.8%) had 4 points and were classified as Mild Inefficient Adaptation (Group 2) , 17 (11.8%) had 5 points and were classified as Effective Adaptation (Group 1) and no participant had classified in Group 4 or in Group 5. The two applications showed the same EDAO adequacy of responses to the effected areas, Affective-Relational, Productivity and Socio-Cultural, and but showed differences in the organic sector. It was found that the routine of work and study is not a contributing factor to the ineffectiveness adaptive, but the feelings that involve studies and work activity. By revealing positive and significant correlation, this study found the statement of Simon (2005) that adaptive sectors interact. Based on the work of Simon (1989, 2005) and Gandini (1996), this research contributed to the implementation of the safety adaptive devise a method for assessing adaptive effectiveness of a larger population in a single moment in time.